Is there a U.S.–China–India triangle? – Beijing's official views. Issue 4 (8th August 2019) - Korolev, Alexander; Wu, Fengshi
ABSTRACT: This research examines China's official perspectives on, and interpretation of, U.S.-China-India relations by surveying official, quasi-official, and some most relevant scholarly publications. China's official line has always emphasized the bilateral nature of the relationship between China and India fending off any third-party interference, including that from the United States. Neither Chinese leaders nor the regime's official media outlets would speak of China–India relationship with a triangular framework (with a rare exception of the Russia–India–China triangle). In the context of the rapid evolvement of U.S.-India military cooperation, the Chinese official line remains unforthcoming about whether such developments have direct implication for China's security or national interests. Chinese core official media has in fact minimized the popularization of the idea that containing China is the driving force behind any cooperation between India and the United States.